Research status and trends of functional magnetic resonance imaging technology in the field of acupuncture: a bibliometric analysis over the past two decades - Wang, Zhongke; Chen, Lu; Jiang, Tianyu; Zhang, Qi; Zhao, Jinying; Wang, Fuchun (Frontiers in Neuroscience, 2025)
ObjectiveAlthough fMRI has been widely used in the field of acupuncture. However, the literature analysis in this field still has significant differences. This study summarizes the current status of functional magnetic resonance imaging (fMRI) in the field of acupuncture and moxibustion and predicts its future trends through Web of Science bibliometric analysis.MethodsThis study uses “fMRI” and “acupuncture” as keywords to search for literature related to functional magnetic resonance imaging (fMRI) in acupuncture research in the Web of Science Core Collection database from January 1, 2004, to April 30, 2024. Visualization analyses were conducted using Citespace (version 6.3 R1) and VOSviewer (version 1.6.20). Citespace was employed to analyze annual publications, countries, institutions, keywords, and co-cited references. VOSviewer was used to analyze authors and co-cited authors, as well as journals and co-cited journals.ResultsFrom 2004 to 2024, a total of 967 publications were retrieved, of which 557 were included after screening. Despite annual fluctuations, the overall trend shows an increase. China and the Chinese Academy of Sciences are the countries and institutions with the highest number of publications, with Tian, J being the author with the most publications, and Kong, J having the highest Co-citation frequency. The article by Dhond, RP, published in 2008, has the highest Co-citation frequency among the co-cited literature. Evidence-based Complementary and Alternative Medicine is the journal with the most publications, while Neuroimage is the co-cited journal with the highest citation frequency. Keyword co-occurrence and burst reveal the main research hotspots, including the diversity of intervention methods, cortical activation, mechanisms related to pain-associated diseases, and brain-related diseases. Keyword burst detection reflects emerging trends, including meta-analysis and systematic reviews, the relationship between ischemic stroke and women, and the connection between mild cognitive impairment and prevention.ConclusionThis study employs bibliometric methods to explore the current status, research hotspots, and frontier issues regarding the application of functional magnetic resonance imaging (fMRI) technology in the field of acupuncture, providing new perspectives and directions for acupuncture fMRI research.